Loss of glyoxalase 2 alters the glucose metabolism in zebrafish - Tabler, Christoph Tobias; Lodd, Elisabeth; Bennewitz, Katrin; Heim, Chiara; Erben, Vanessa; Schröder, Hannes; Poth, Tanja; Fleming, Thomas; Morgenstern, Jakob; Haußer-Siller, Ingrid; Sticht, Carsten; Poschet, Gernot; et al. (Redox Biology, 2023)
Glyoxalase 2 is the second enzyme of the glyoxalase system, catalyzing the detoxification of methylglyoxal to d-lactate via SD-Lactoylglutathione. Recent in vitro studies have suggested Glo2 as a regulator of glycolysis, but if Glo2 regulates glucose homeostasis and related organ specific functions in vivo has not yet been evaluated. Therefore, a CRISPR-Cas9 knockout of glo2 in zebrafish was created and analyzed. Consistent with its function in methylglyoxal detoxification, SD-Lactoylglutathione, but not methylglyoxal accumulated in glo2−/− larvae, without altering the glutathione metabolism or affecting longevity. Adult glo2−/− livers displayed a reduced hexose concentration and a reduced postprandial P70-S6 kinase activation, but upstream postprandial AKT phosphorylation remained unchanged. In contrast, glo2−/− skeletal muscle remained metabolically intact, possibly compensating for the dysfunctional liver through increased glucose uptake and glycolytic activity. glo2−/− zebrafish maintained euglycemia and showed no damage of the retinal vasculature, kidney, liver and skeletal muscle. In conclusion, the data identified Glo2 as a regulator of cellular energy metabolism in liver and skeletal muscle, but the redox state and reactive metabolite accumulation were not affected by the loss of Glo2.
Online veröffentlicht am 14. Dezember 2022, Dateiversion vom 17. Dezember 2022
Gesehen am 01.02.2023